(untitled) (Damu Journal of Sport Sciences, 2025)
The research aims to develop a scale of school engagement among physical education teachers in the center of Diwaniyah Governorate. The research problem lies in the following question: What is the role of developing school engagement among physical education teachers in the center of Diwaniyah Governorate? The researcher identified the research community and sample, which are all physical education teachers in the General Directorate of Education in the center of Diwaniyah Governorate, who are regular for the academic year (2024-2025), and their number is (420) male and female teachers, by consulting with the Planning Division in the General Directorate of Education in Diwaniyah. The sample for the scale was (200) male and female teachers, and the exploratory sample was (20) male and female teachers, and they were selected using the random stratified method. Conclusions: School interaction is at a good level among male and female physical education teachers in the center of Diwaniyah Governorate, and there is good interest from the schools of the center of Diwaniyah Governorate in what helps to increase school interaction among male and female physical education teachers. There is a preference for the variables of certificate and experience among physical education teachers in the center of Diwaniyah Governorate. Recommendations: Paying attention to school interaction among physical education teachers in the center of Diwaniyah Governorate, holding seminars and training workshops for physical education teachers because of their benefit in developing school interaction and classroom activities in physical education lessons, activating the role of physical education teachers and students through Collecting ideas, questions, and inquiries during the physical education lesson using statistical methods. The data obtained was processed using the statistical package (SPSS) and the Excel program.